Elevation of brain magnesium with Swiss chard and buckwheat extracts in an animal model of reduced magnesium dietary intake. (2nd December 2022) - El-Khodor, Bassem F.; James, Karma; Chang, Qing; Zhang, Wei; Loiselle, Yvette R.; Panda, Chinmayee; Hanania, Taleen
ABSTRACT: Objectives: Inadequate dietary magnesium (Mg) intake is a growing public health concern. Mg is critical for diverse metabolic processes including energy production, macromolecule biosynthesis, and electrolyte homeostasis. Inadequate free Mg 2+ ion concentration ([Mg 2+ ]) in the brain is associated with several neurological and behavioral disorders. Elevating [Mg 2+ ]in the brain using oral Mg supplementation has proven to be challenging due to the tight regulation of Mg 2+ transport to the brain. This study explored the effect of short-term moderate reduction in dietary Mg intake (87% of normal Mg diet for 30 days) on [Mg 2+ ] in the cerebrospinal fluid (CSF) ([Mg 2+ ]CSF ) and red blood cells (RBCs) ([Mg 2+ ]RBC ) in adult male rats. In addition, we investigated the effectiveness of magnesium-rich blend of Swiss chard and buckwheat extracts (SC/BW extract) in increasing brain [Mg 2+ ] compared to various Mg salts commonly used as dietary supplements. Methods: Animals were assigned to either normal or low Mg diet for 30 - 45 days. Following this, animals maintained on low Mg diet were supplemented with various Mg compounds. [Mg 2+ ]CSF and [Mg 2+ ]RBC were measured at baseline and following Mg administration. Anxiety-like behavior and cognitive function were also evaluated. Results: The present study showed that a short-term and moderate reduction in Mg dietary intake results in a significant decline in [Mg 2+ ]CSF and [Mg 2+ ]RBC and the emergence of anxiety-like behavior in comparison to animals maintained on normal Mg diet. Supplementation with SC/BW extract significantly elevated [Mg 2+ ]CSF and improved animal performance in the novel object recognition test in comparison with animals maintained on reduced Mg intake and supplemented with various Mg compounds. Discussion: These observations indicate that brain [Mg 2+ ] is more sensitive to a short-term and moderate reduction in Mg dietary intake than previously thought and emphasizes the importance of dietary Mg in replenishing brain Mg 2+ reserves.